Model Pembelajaran Problem Based Learning dengan Media Papan Bilangan Wonderful Semarang Meningkatkan Kemampuan Literasi Numerasi Siswa Sekolah Dasar - Mega Ega Wardani; Panca Dewi Purwati (Journal on Education, 2025)
This study aims to analyze the impact of implementing the Problem-Based Learning (PBL) model assisted by the Wonderful Semarang number board media on the numeracy literacy skills of third-grade students at SD Negeri Kalibanteng Kidul 01. The research employed a quantitative method with a one-group pretest-posttest design, involving 30 students as research subjects. A multiple-choice test instrument was used to measure numeracy literacy skills before and after the intervention. The results showed that the average pretest score of 40.33 increased to 85.67 in the posttest, with an average gain score of 0.76, categorized as high. The t-test indicated a significant difference between pretest and posttest scores (p < 0.05), demonstrating the effectiveness of the PBL model with this innovative media. In conclusion, the combination of PBL and the Wonderful Semarang number board media effectively improved students' numeracy literacy skills, making learning more engaging and contextually relevant.